Penerapan Sistem Accurate Dalam Penyusunan Laporan Keuangan: Studi Kasus Pada Umkm Afifa Laundry - Ananda, Disa Laviana; Roup, Abdul (Jurnal Informatika Kesatuan, 2022)
In this era of increasingly transparent and open globalization, it has brought all the activities of human life into tight competition in the field of technology.The impact of technological developments on work activities is that many people from all walks of life use computers.Incorrect use of computerized technology is in accounting information system in a company. The role of accounting information systems helps enterprise leaders make management decisions by organizing documents and notes, resulting in precise and accurate financial report information to facilitate the management of corporate activities. This research aims to determine the application of accurate systems can assist in the preparation of financial statements and analyze whether there is weakness of the system that is running.The author conducts research at Afifa Laundry, Jl. Raya Laladon Indah No.7 Bogor. This research uses qualitative methods of descriptive. The Data used in this research was obtained through interviews, observations, and documentation conducted at Afifa Laundry. Based on the results of the implementation of a new computer-based accounting information system at Afifa Laundry has made a very positive impact for the company, starting with a neat customer number, the existence of a sales invoice, and the absence of a feedstock in the registration of invoices and companies can control the finances of costs and revenues, and can easily generate financial statements. Key Words: Accounting information System and Accurate Accounting Software version 5